2012
DOI: 10.3109/01677063.2012.674993
|View full text |Cite
|
Sign up to set email alerts
|

KCNH2 Gene Mutation: A Potential Link Between Epilepsy and Long QT-2 Syndrome

Abstract: Long QT syndrome (LQTS) is closely associated with syncope, seizure, and sudden death but LQTS is frequently misdiagnosed as epilepsy. LQTS and epilepsy both belong to the group of ion channelopathies that manifest in the heart and brain. Therefore, genetic analysis of genes associated with potassium and sodium homeostasis and electrical disorders may reveal a link between epilepsy and lethal cardiac arrhythmia. Here, the authors report a young woman who suffered recurrent seizure episodes and syncopes that oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 23 publications
1
40
0
2
Order By: Relevance
“…4 In this era of increased awareness of LQTS, a real risk of overdiagnosis of generalized seizure-like spells as cardiogenic syncope is emerging, which may subsequently lead to lifestyle alterations, unnecessary medications, and ultimately invasive procedures with implantation of unnecessary devices. This overdiagnosis of LQTS seems ever present, as recently, we demonstrated that 40% of the patients that came to Mayo Clinic with the diagnosis of LQTS left our institution without that diagnosis.…”
Section: Epilepsy Misdiagnosed As Long Qt Syndrome E137mentioning
confidence: 99%
“…4 In this era of increased awareness of LQTS, a real risk of overdiagnosis of generalized seizure-like spells as cardiogenic syncope is emerging, which may subsequently lead to lifestyle alterations, unnecessary medications, and ultimately invasive procedures with implantation of unnecessary devices. This overdiagnosis of LQTS seems ever present, as recently, we demonstrated that 40% of the patients that came to Mayo Clinic with the diagnosis of LQTS left our institution without that diagnosis.…”
Section: Epilepsy Misdiagnosed As Long Qt Syndrome E137mentioning
confidence: 99%
“…The proteins that are coded in the KCNH2 gene are also found in ion channels in the astrocyte membrane of the hippocampus. This association is postulated as a possible explanation for the link between long QT syndrome and epilepsy (14)(15)(16)(17). Further, it is shown that patients with long QT syndrome type 2 more often have a history that includes epileptic seizures and are more often treated with antiepileptic drugs than patients with long QT syndrome types 1 and 3 (17).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical background for the assumption of a common pathophysiological substrate between epilepsy and long QT syndrome has mainly been limited to case reports (13)(14)(15)(16). The proteins that are coded in the KCNH2 gene are also found in ion channels in the astrocyte membrane of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with recurrent convulsions who were treated for epilepsy for years were finally diagnosed with LQT (Gatto et al, 1993;Scheepers et al, 1998;Medina-Villanueva et al, 2002;Hunt and Tang, 2005;Johnson et al, 2009;MacCormick et al, 2009;Jorge et al, 2011). Although the responsible genes of the two channelopathies are different, besides misdiagnosis, increasing evidence argues for a close pathogenic relationship between LQT2 and epilepsy (Johnson et al, 2009;Keller et al, 2009;MacCormick et al, 2009;Omichi et al, 2010;Zamorano-Leon et al, 2012). For example, in a chart review study (Johnson et al, 2009), a seizure phenotype was observed in 98 patients among 343 LQT patients (98/343, 29%).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a common misdiagnosis of LQT2 versus epilepsy (Johnson et al, 2009;MacCormick et al, 2009). In some cases, seizures of LQT2 are likely due to cardiac syncope (Keller et al, 2009;Jorge et al, 2011;Zamorano-Leon et al, 2012). In addition, increasing evidences suggest LQT2 and epilepsy coexist (Johnson et al, 2009;MacCormick et al, 2009;Jorge et al, 2011).…”
Section: Introductionmentioning
confidence: 99%